Algerian Commercial Law in Light of Recent Amendments -Business Transactions, Merchant Theory, E-Commerce, Commercial Establishments: ISBN 978-630-95064-3-6 - Souiki, Horiya (Technium Books, 2025)
The book: Algerian Commercial Law in Light of Recent Amendments - Business Transactions, Merchant Theory, E-Commerce, Commercial Establishments- ISBN 978-630-95064-3-6 is published in Technium.